Co-determination as a road to goal commitment: managing Danish high schools - Staniok, Camilla Denager (Politica, 2016)
Goal-setting initiatives have become an integrated part of managing public organizations in Denmark. The purpose is often to align employee effort with managerial goal prioritization and to motivate all employees to work in the same direction. This is particularly important in public organizations where employees are met with multiple and conflicting performance demands. The question is, though, how managers can ensure that employees are committing to the same goal as the managers prioritize? Employee co-determination has a potential to foster and direct employees’ goal commitment by increasing the dialogue between managers and employees and by legitimizing managers’ goal prioritization. The role of co-determination has so far been neglected in studies of goal-setting initiatives. In this article a qualitative study of ten managers and employees provides a nuanced picture of what co-determination means in the Danish educational sector, and analyses of two parallel surveys of 73 principals and 1353 teachers show that employee co-determination has a significant positive effect on the association between principals’ prioritization of high school completion rates and the teachers’ commitment to this goal.